Percutaneous Cystolithotripsy As A Reliable Modality To Treat Pediatric Vesiculolithiasis - Gupta, Dipesh Kumar; Mishra, S M (Journal of Nepalgunj Medical College, 2017)
Background: Primary vesical stones are common in children in underdeveloped and developing countries. The treatment options available for managing bladder calculi include transurethral cystolithotripsy, open cystolithotomy and shock wave lithotripsy (SWL). Although the majority of vesical calculi in adults can be treated by transurethral lithotripsy, this procedure is restricted in children due to the narrow caliber of the urethra. For this reason, percutaneous cystolithotripsy (PCCL) is a good choice as a safe and effective method for the treatment of bladder stones in children. Aim of the Study: The study was aimed to evaluate outcome of PCCL in pediatric population coming with vesiculolithiasis in our center. Materials and Methods: Pediatric age group patients diagnosed as vesical calculus were undertaken for PCCL. Ten patients who presented between November 2014 to December 2015, were included. The procedure was done under general anesthesia. After performing cystoscopy, suprapubic puncture was made and tract dilated up to 26 Fr. Nephroscope was used for visualization and pneumatic lithotripsy for fragmentation of the stone followed by removal of st nd all fragments. Perurethral and suprapubic catheters were placed at the end to be removed on 1 and 2 post operative day, respectively. Results: Median age of the patients was 5.5 (3-13) years. Majority were male patients from hilly region of western Nepal. Mean stone size was 15 mm. All patients were rendered stone free with average operative time of 32.2 minutes. Except one minor complication of mucosal injury patients were discharged after mean hospital stay of 3.9 days. Conclusion: Percutaneous suprapubic lithotripsy is a safe and effective method for the treatment of bladder stones in children. It is fast and associated with negligible complications. JNGMC Vol. 14 No. 1 July 2016, Page: 18-20